Enhancing the Quality of Educational Sciences Programs in Jordanian Universities According to CAEP Standards - Khrisat, Zaid (International Journal of Interactive Mobile Technologies (iJIM), 2024)
This study aimed to evaluate the quality of educational sciences programs in Jordanian universities according to the Council for the Accreditation of Educator Preparation (CAEP) standards. The study included academic leaders and faculty members from all public and private educational sciences colleges in Jordanian universities, totaling 817 participants. A random sample was selected, comprising two public and two private universities from each region. A questionnaire based on CAEP standards was developed, containing 46 items across five standards, and distributed to 508 participants. The study used a developmental survey methodology, revealing that the quality of educational sciences programs was moderate across all standards, with an average score of 3.07 and a standard deviation of 0.39. The quality assessment varied by region, gender, academic rank, and type of university, with significant differences favoring the central region for college quality and continuous improvement, females, associate professors for program impact, and public universities.